REFRAMING CHARACTER ROLES: DEFAMILIARIZATION OF PROTAGONIST AND ANTAGONIST IN AWAL DAN AHIR BY NAGUIB MAHFOUZ - Masadi, M. Anwar; Hikmah, Mei Wakhidatul; Al Humairoh, Jihan (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2025)
Defamiliarization is the study of how the literary work becomes strange and foreign, differs from the others. This qualitative descriptive study uses Victor Shklovsky’s Defamiliarization theory to see the opposition characters created by Najib Mahfudz in Awal dan Ahir. The result of this study is that Najib Mahfudz creates unique characters such as Nafisah, a mother who was abandoned by her husband in the face of social and economic situations with her four children after the revolution in Egypt. The protagonist characters such as Samirah, Hasanain, Husain, Nafisah, Bahia and Farid Affandy, represent the typical characters created by Mahfudz along with his social and psychological situations. Likewise, the Antagonist characters are so uniquely created by Mahfudz. The social situation, political economy and psychology of Egyptian society also colour the distinctive characters of the story. The characters created by Najib Mahfudz both from the antagonist and the protagonist are very interesting structurally, the characters built by both protagonist and antagonist are not directly related but meet in other forms of social relationships, which is different from other novels in terms of generally. Najib Mahfudz seems very good at making different characters so that it appears that these characters come to life in front of the reader.